Human capital effects of kindergarten and school enrolment timing - Ágnes Szabó-Morvai; Dániel Horn; Anna Lovász; Kristof De Witte (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2017)
Using instrumental variables approach this paper studies the effect of kindergarten starting age jointly with that of school starting age. We show that estimating the effect of kindergarten or school enrolment timing on later human capital outcomes separately, without taking their inter-relatedness into account, may confound the two effects and produce endogenous results. The instruments originate from exogenous birthdate-related enrolment cutoffs in kindergarten and school admissions. Using a rich Hungarian database, we show that both earlier kindergarten enrolment and later school enrolment have a significant and non-negligible positive effect on standardised test scores in grade 6, 8, and 10, class marks given by the teacher, aspirations for higher education, and track choice. These effects tend to decrease over time and are heterogeneous across mother's education, as earlier kindergarten enrolment age seems to matter only for the children of low educated mothers.
Keywords: I21; I26; 330; Kindergarten enrolment age; School enrolment age; Instrumental Variables